KONTRIBUSI USAHA MADU TERHADAP KESEJAHTERAAN PELAKU USAHA MADU DI KOTA BANDAR LAMPUNG - Fitrisyah, Anisa Azzahra; Prasetyo, Agus Subhan; Mariyono, Joko (Jurnal Agribisnis Wijaya Putra Surabaya, 2022)
Welfare is a measuring point for an individual who has achieved a prosperous condition, which is certainly the goal. A study on the contribution of the honey business to the welfare of honey entrepreneurs was carried out from March to April 2022 in Bandar Lampung City. The location selection was determined purposively with the consideration that the Bandar Lampung City was an area where there are many entrepreneurs who develop honey product businesses than in the other surrounding areas. This study aims to determine the contribution of honey business to the household income of honey entrepreneurs in Bandar Lampung City and to determine the level of welfare of honey entrepreneurs' households in Bandar Lampung City. The research method used in this study is a descriptive method with a quantitative approach. The analyzes used include income analysis, expenditure analysis and the level of welfare of honey entrepreneurs. The respondent determination method used in this research is snowball sampling. The results showed that the contribution of honey business income to the household income of honey entrepreneurs in Bandar Lampung City was still relatively low at 19%. This is because most entrepreneurs still make honey business as a side business. The level of household welfare of honey entrepreneurs in Bandar Lampung City is classified as a prosperous condition.